Knowledge of cancer genetics and attitudes about genetic counseling and testing: a randomized trial of the Know Your Risk intervention compared to conventional genetic counseling - Mira L. Katz; Patrick M. Schnell; Paul L. Reiter; Leigha Senter; Amber Aeilts; Christina Spears; Julia Cooper; Jordan Brown; Kate P. Shane-Carson; Doreen M. Agnese; Amanda E. Toland; Kevin Sweet (Cancer Causes & Control, 2026)
Purpose To determine if the developed Know Your Risk (KYR) intervention is similar to conventional genetic counseling; we evaluated participants’ knowledge of cancer genetics, breast cancer risk perception, attitudes about genetic counseling and testing, and satisfaction with genetic counseling. Methods Women ( n = 866) who screened at elevated risk for breast cancer were randomized to the KYR intervention or conventional genetic counseling (2022–2024). The KYR intervention included a series of online pre-test educational videos, direct access to genetic testing, and patient preference for receiving post-test genetic counseling. Participants completed surveys at baseline and after genetic counseling and testing. Non-inferiority hypothesis testing compared the two participant groups. Results The mean knowledge score (range 0–12) increased in both study groups from a baseline mean of 6.87 (standard deviation (SD) = 2.46) to 8.66 (SD = 2.16) for the KYR intervention and 8.56 (SD = 2.14) for conventional counseling. Additionally, statistical analyses suggest the non-inferiority of the KYR intervention for participants’ accuracy of their breast cancer risk, attitudes about genetic counseling and genetic testing, and satisfaction with genetic counseling compared to participants randomized to conventional genetic counseling. Conclusion Findings support that the components included in the KYR intervention are non-inferior for cancer genetic knowledge, risk perception, genetic counseling and testing attitudes, and genetic counseling satisfaction among women who screen at elevated risk for breast cancer. By using the combination of components included in the KYR intervention, genetic counseling and genetic testing are more accessible, convenient, and patient-driven. Trial Registration : ClinicalTrials.gov Identifier: NCT05325151.

Retrospective chart analysis to determine the impact of a patient-facing digital risk stratification tool combined with a clinical screener for hereditary cancer genetic risk assessment triage in a community oncology clinic - Kate P. Shane-Carson; Douglas Smith; Angie Smith; Caroline Seeley (Journal of Community Genetics, 2023)